Respuesta :

Answer:

[tex]\sqrt{221}[/tex]

Step-by-step explanation:

Using the distance formula:

[tex]d=\sqrt{(8-(-6))^2+(3-(-2))^2}=\sqrt{14^2+5^2}=\sqrt{196+25}=\sqrt{221}[/tex]

Hope this helps!

Answer:

[tex]\sqrt{221}[/tex]

Step-by-step explanation:

The distance formula is:

[tex]d = \sqrt{(x_2 - x_1)^2 + (y_2-y_1)^2}[/tex]

where (x1, y1) are the coordinates of the first point, and (x2,y2) are the coordinates of the second point.

The point X is at (-6,3). The point Y is at (8, -2). Therefore, we can plug these points into the formula.

[tex]d = \sqrt{(8 - (-6))^2 + (-2-3)^2}[/tex]

First, solve inside the parentheses

[tex]d = \sqrt{(8+6)^2 + (-2-3)^2}[/tex]

[tex]d = \sqrt{(14)^2 + (-5)^2}[/tex]

Solve the exponents.

14^2=14*14=196

[tex]d=\sqrt{196+(-5)^2}[/tex]

-5^2=-5*-5=25

[tex]d=\sqrt{196+25}[/tex]

Add 196 and 25

[tex]d=\sqrt{221}[/tex]

d=14.8660687473

The distance between the points is [tex]\sqrt{221}[/tex] or about 14.87